Doing it Old School: Peer-led occupational safety training in the U.S. construction Industry - Sinyai, Clayton; Stafford, Pete; Trahan, Chris (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
Many labour organizations that sponsor occupational health and safety training champion “peer training,” preferring instructors drawn from the shopfloor over academically credentialed experts. But peer training is hardly new: in the skilled trades, master craftsmen have instructed apprentices since the Middle Ages. Building on the apprenticeship model of education, the U.S.-based construction unions have created a network of more than 4,000 peer trainers who provide occupational health and safety training to up to 100,000 men and women in the building trades each year.